Effects of distance to the sea and geomorphological characteristics on the quantity and distribution of microplastics in beach sediments of Granada (Spain) - Godoy, Verónica (2020)
Microplastics became an unprecedented challenge and mapping their contamination all over the world is needed in order to establish baseline levels and identify the polymers in order to enhance adequate legislation and policy. The main objective of this study is to demonstrate the existence of microplastic pollution on three beaches on the coast of Granada (Spain), namely La Herradura, Motril Beach and La Rábita, characterizing the particles and the relationships in their distribution. This may contribute supporting the studies carried out at a national level in accordance with the Directive on Marine Strategy (2008/56/EC). The results showed a greater median concentration of particles/kg of dry sediment in La Herradura (45.0 ± 24.7) than in Motril (31.5 ± 21.5) and La Rábita (22.0 ± 23.2). These data revealed a higher contamination by microplastics in an enclosed bay-type beach (La Herradura) in comparison with open delta-type beaches. The predominant morphologies were microspheres and fragments, with maximum median concentrations of 38.0 ± 23.7 and 6.0 ± 0.7 particles/kg, respectively. The distribution and size of the particles is affected by the geomorphological and sedimentary characteristics of these beaches, which are different from any other in Spain and in the Mediterranean in general. The beaches of Granada showed more microplastic contamination than Greek or Slovenian beaches, but less than other Spanish beaches. In this area of the Mediterranean, the presence of microplastics can be affected by the wind, sea currents or methodological aspects such as the pore size of the filters used. All of these factors were analysed when comparing the beaches of Granada with other Mediterranean beaches. This study shows that there is contamination by microplastics on the beaches of Granada, which have been little explored until now due to the difficult geological and granulometric characteristics, and gives support to other national studies.